Exploring Key Insights for the Future in Agricultural Policy Research for Sustainability - Imam Hanafi; Puji Wahyu Mulyani; Effy Roefaida; Loso Judijanto (West Science Interdisciplinary Studies, 2023)
This research employs bibliometric analysis to explore key insights for the future in agricultural policy research, with a focus on sustainability. The study delves into publication trends, citation patterns, co-authorship networks, and keyword analyses to unravel the intricate landscape of scholarly contributions. The most-cited works, spanning seminal contributions to participatory action research and sustainable rural livelihoods, reveal foundational texts that have shaped the field. Clustering analysis elucidates thematic concentrations, ranging from climate change and artificial intelligence to biodiversity and education. Furthermore, the occurrence of terms such as "Common Agricultural Policy" and "Governance" underscores the central role of policy frameworks and collaborative decision-making in agricultural sustainability. The abstract concludes by highlighting the implications of these findings for future research directions and policy formulations, emphasizing the interdisciplinary and transformative nature required for sustainable agricultural practices.